Winning Hearts and Minds Through a Policy Promoting the Agroecological Paradigm in Universities - Ricardo Serra Borsatto; Vanilde Ferreira Souza-Esquerdo; Henrique Carmona Duval; Fernando Silveira Franco; Fabio Grigoletto (Universidade Federal do Norte do Tocantins, 2022)
Brazil stands out at the global level for having implemented several policies intending to promote agroecology as a productive paradigm for small-holder farmers. However, the impacts of this process of institutionalization of agroecology still lack research and debates that evaluate the effectiveness of these policies. In this paper, we assess and discuss the impacts of a policy specifically focused on education in agroecology, the support to the establishment of Centers for the Study of Agroecology and Organic Production (NEAs) in higher education institutions throughout Brazil. NEAs bring together teachers, researchers, and students who engage in teaching, research, and extension activities in partnerships with peasant farmers, their organizations, and rural extension workers. The hypothesis that guides our analysis is that this support to establish NEAs allowed redistribution of symbolic power in the universities where they were established, supporting agroecology to gain greater legitimacy inside and outside the university field. Based on an in-depth study of four NEAs, the NEAs are evaluated from the perspective of social fields in dispute. Our findings suggest that the State support to university groups dedicated to the promotion of agroecology has allowed the construction of what we have named agroecological spaces, which symbolically dispute the dominant paradigms in educational institutions, supporting the constitution of agroecological territories.